Supplementation of feed blocks to the basal diet of native forage improves digestibility and ruminal fermentation in late-gestation sheep - Tresia, Gresy Eva (2025)
The nutrient content of available native fodders for sheep under tropical conditions is low, while the nutrient requirements of sheep, particularly during late pregnancy, are high. This study aimed to enhance the nutritive value of various indigenous fodders using formulated feed block supplementation to address nutrient insufficiency in late-pregnant crossbred Batur sheep. Five basal diets were formulated from native fodders with and without feed blocks supplementation (FS). Treatments were arranged in a 5 × 2 factorial design, with the first factors being five basal diets and the second factors being supplementation with and without feed block. Each treatment had six replicates. The results showed significant interactions effect (p < 0.01) between the basal diets and supplementation on in vitro digestibility, ruminal pH value, NH3-N, total volatile fatty acids (VFA) concentration, total gas production, total bacterial and protozoa population. The highest response of FS in terms of increased digestibility and total VFA production was observed in the basal diet comprising a 1:1 ratio of dwarf elephant grass and Galinsoga (Galinsoga parviflora) (P4). Feed block supplementation decreased protozoa and bacterial populations in most treatments but tended to increase methane emissions (p = 0.6947). The protozoa population decreased sharply in the P2 basal diet (native grass, carrot leaves, and white hoarypea (Tephrosia candida (Roxb.) DC), while the bacterial population increased significantly in the P4 basal diet. In conclusion, feed block supplementation to native fodder mixture basal diet improves feed digestibility and rumen fermentation to overcome nutrient insufficiency in late-pregnant crossbred Batur sheep.